HUBUNGAN STIGMA HIV/AIDS DENGAN PEMANFAATAN KLINIK VCT PADA WANITA PEKERJA SEKS DI BANDUNGAN KABUPATEN SEMARANG - , FITRI INDRAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The spread of HIV in Indonesia is still concentrated in key populations, one of which are female sex workers. In Indonesia, commercial sex is a major cause of the spread of HIV after injecting drug use. One service that fuctions in preventing the spread of HIV is VCT clinic. VCT clinics are ongoing HIV care facilities, where service is based on the clientâs needs and performed voluntarily without any coercion. Objective:To identify association between HIV/AIDS-related stigma and VCT clinic utilization among female sex workers in Bandungan Semarang District. Method: The study used cross sectional design. The population was all female sex workers that work in Bandungan. The samples were female sex workers that met the criteria for inclusion and exclusion.Data analysis used univariable analysis, bivariable analysis with chi-square statistical tests p <0,05 and CI 95% significance level, and multivariable analysis with logistic regression. Result: HIV/AIDS-related stigma dimensions âblame & judgmentâ was significantly associated with utilization of VCT clinics with OR 5,2 (95% CI 1,08- 25,38). HIV/AIDS-related stigmadimensions âinteractionâ was significantly associated with utilization of VCT clinics with OR 4,2 (CI 95% 1,31-13,75). The result of bivariate analysis showed significant association between knowledge of HIV/AIDS with p value 0,000 and PR 1,9 (CI 95% 1,37-2,64) and utilization of VCT clinic. The result of logistic regression analysis showed lower HIV/AIDSrelated stigma had the probability of increasing utilization of VCT clinic as much as 30% after being controlled by variables of knowlegde of HIV/AIDS. Conclusion: HIV/AIDS-related stigma was associated with utilization of VCT clinics. The lowerHIV/AIDS-related stigma resulted in the greater chance of utilizing VCT clinic.